Disseminated intravascular coagulation with massive pulmonary thromboembolism in a male newborn of a SARS CoV-2 positive mother - Simovic, Aleksandra; Prodanovic, Tijana; Mihajlovic, Zorica; Savic, Dragana; Zivojinovic, Suzana; Cekovic Djordjevic, Jelena; Prodanovic, Nikola S; Stojkovic, Andjelka (Medicinski časopis, 2024)
Introduction Immune and physiological changes that occur during pregnancy may increase the risk of developing serious SARS CoV-2 infections. Case report We want to present a non-infected newborn with 5-minute Apgar score of 8 who developed massive pulmonary thromboembolism in the first 36 hours of being born, from a SARS CoV-2 positive mother without any symptoms. Conclusion Careful monitoring of newborn and determination of the coagulation status and inflammation markers on a daily basis could be justified in SARS CoV-2 positive pregnancy.
Keywords: SARS CoV-2 инфекције; тромбоемболијске компликације; новорођенче